ADVANCING ENVIRONMENTAL PROTECTION: ENHANCEMENTS TO RURAL SEWAGE SYSTEMS IN TONG'AN DISTRICT, XIAMEN - Wang, Jianyu (Ayden International Journal of Basic and Applied Sciences, 2024)
In 2021, Xiamen City embarked on an ambitious endeavor to advance the high-quality and high-standard enhancement and treatment of rural domestic sewage, aligning these efforts with the broader goals of rural revitalization. The comprehensive project aims to address rural domestic sewage issues, leveraging a tailored approach suited to the local context. The objective is to achieve a significant milestone by the first half of 2022: the effective segregation of rainwater and sewage in rural areas and the full collection and treatment of rural domestic sewage. Given the unique challenges of rural regions, characterized by dispersed settlements, smaller populations, and modest economies, conventional urban governance models are insufficient to meet the demands of "green development" in these areas. As a solution, the implementation of a "one village, one policy" strategy emerges as a vital component in the treatment of rural sewage, effectively tailoring solutions to the distinctive characteristics of each village.